Chemical-mechanical polishing composition and chemical-mechanical polishing method using the same

KR103021604B1Active Publication Date: 2026-09-18ENTEGRIS INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
KR1020227023918
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-13
Filing Date
2020-12-07
Publication Date
2026-09-18
Estimated Expiration
2040-12-07

Smart Images

  • Figure 112022072391134-PCT00009_ABST
    Figure 112022072391134-PCT00009_ABST
Patent Text Reader

Abstract

The chemical-mechanical polishing composition of the present invention is for polishing a substrate and contains an abrasive, hydroxyethyl cellulose having a weight average molecular weight of 200,000 or less, a basic component, a surfactant, and an aqueous carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a chemical-mechanical polishing composition and a chemical-mechanical polishing method using the same. Background Technology

[0002] Substrates such as silicon wafers used in the manufacture of semiconductor devices have strict surface quality requirements, and to ensure high surface quality, Chemical-Mechanical Polishing (CMP) technology has been used in the past. Generally, CMP of substrates such as silicon wafers involves multiple steps, including, for example, a pre-polishing step and a final polishing step. In the final polishing step following the pre-polishing process, conventionally, the surface quality of the substrate, such as surface defects and haze characteristics, was improved by using a polishing composition (also called a CMP slurry) with weaker polishing power than that of the pre-polishing process.

[0003] Surface defect inspection devices are generally used to manage surface defects on substrates such as silicon wafers. Defects detected by surface defect inspection devices include foreign substances and residues on silicon wafers that are not removed during polishing steps or subsequent rinsing steps. As such surface defect inspection devices, devices that irradiate light, such as laser light, onto the substrate surface and detect reflected or scattered light generated from the substrate surface to detect the presence or absence of defects on the substrate surface are generally known.

[0004] When such strong light is irradiated onto the surface of a substrate, clouding may occur due to diffuse reflection caused by the roughness of the substrate surface. This clouding is called haze, and since haze is closely related to the surface roughness of the substrate, it can be used as an indicator of surface roughness. Recently, due to the rapid development of surface defect inspection devices, nano-level surface defects can be observed. However, if haze is present on the substrate surface, the diffusely reflected light caused by the haze becomes background noise, which can interfere with defect detection by the surface defect inspection device.

[0005] In order to reduce the surface defects and haze described above, it is important to manage the chemical-mechanical polishing composition used in the finishing polishing step, and more specifically, to manage the CMP slurry actually supplied to the substrate during use (polishing). In chemical-mechanical polishing compositions for CMP of substrates such as silicon wafers, it is known to use abrasives such as silica or basic compounds such as ammonia (e.g., Patent Documents 1 and 2) in addition to using hydroxyethyl cellulose (HEC) as a water-soluble polymer to improve the wettability of the substrate surface. In this regard, techniques using other water-soluble polymers as alternatives to HEC are also disclosed (e.g., Patent Document 3).

[0006] [List of Cited Bibliographies]

[0007] [Patent Document 1] Japanese Unexamined Patent Publication No. 2015-159259

[0008] [Patent Document 2] Japanese Unexamined Patent Publication No. 2017-117847

[0009] [Patent Document 3] Japanese Unexamined Patent Publication No. 2013-222863 The problem to be solved

[0010] HEC, which is a cellulose derivative and can be used as a water-soluble polymer in CMP slurries, can improve the wettability of the polishing target surface of a substrate, such as a silicon wafer, and maintain the hydrophilicity of the surface. Therefore, by using HEC, the interaction between the substrate and the slurry can be properly induced, thereby improving the surface quality of the substrate. Since these characteristics of HEC are very effective for finishing CMP polishing of substrates, particularly silicon wafers, and are combined with conveniences such as high dispersibility in aqueous solvents, it is necessary to use HEC in polishing compositions.

[0011] Conversely, to remove aggregates and impurities present in the polishing composition, the CMP slurry is sometimes filtered immediately before CMP is performed. This is called Point-Of-Use (POU) filter filtration and is an efficient process for improving the surface quality of the substrate to be polished. Furthermore, if the pore diameter of the filter is reduced, smaller aggregates can be removed by filtration, thereby further improving the surface quality of the substrate. Therefore, it is desirable to perform POU filter filtration on the polishing composition using a filter with a smaller pore diameter. Specifically, the polishing composition needs to possess excellent filtration capabilities, such as adequately suppressing filter clogging even when using a filter with a small pore diameter. The CMP slurry used for chemical-mechanical polishing can be diluted from its state at the time of purchase or storage, depending on the polishing conditions desired by the user and the specifications required by the substrate. In this case, since the filtration described above is performed with the diluted CMP slurry, it is important to suppress filter clogging and improve the filtration capabilities of the POU filter even after dilution.

[0012] Due to the characteristics of HEC as described above, it is highly desirable to use HEC in slurries, particularly for CMP of silicon wafers. Conversely, in CMP slurries containing abrasives, HEC, and basic components (e.g., ammonia) that are generally used as accelerators for mechanical polishing, HEC tends to adsorb onto abrasives such as silica and form aggregates. Consequently, changes in the mixing ratio due to dilution lead to reduced dispersibility compared to the slurry before dilution, resulting in a tendency for reduced filtration performance. Therefore, in polishing compositions containing HEC, particularly when the composition is diluted, filtration performance is lower compared to polishing compositions that do not contain HEC. This makes it difficult to filter through POU filters with small pore diameters, thereby limiting the improvement of the substrate surface quality. Thus, it is necessary to address the problem of reduced POU filter filtration performance after dilution in CMP slurries containing abrasives, HEC, and basic components.

[0013] Accordingly, the object of the present invention is to provide a chemical-mechanical polishing composition containing HEC that exhibits improved POU filter filtration ability, enabling filtration even with a POU filter having a small pore diameter after dilution, and a chemical-mechanical polishing method using the same. means of solving the problem

[0014] The present invention, capable of achieving the above-mentioned objectives, is as follows:

[0015] (1)

[0016] Abrasive,

[0017] Hydroxyethyl cellulose having a weight average molecular weight of 200,000 or less,

[0018] Basic components,

[0019] surfactant, and

[0020] aqueous carrier

[0021] A chemical-mechanical polishing composition for polishing a substrate comprising

[0022] (2)

[0023] A chemical-mechanical polishing composition in which the hydroxyethyl cellulose in the composition of (1) has a weight average molecular weight of 150,000 or less.

[0024] (3)

[0025] A chemical-mechanical polishing composition in which the abrasive has a primary particle diameter of 50 nm or less, in the composition of (1) or (2).

[0026] (4)

[0027] A chemical-mechanical polishing composition in which the abrasive in the composition of (1) or (2) has a primary particle diameter of 20 to 40 nm.

[0028] (5)

[0029] A chemical-mechanical polishing composition in any one of the compositions of (1) to (4), wherein the surfactant comprises one or more of alkylene polyalkylene oxide amine polymers and polyoxyalkylene alkyl ethers.

[0030] (6)

[0031] A chemical-mechanical polishing composition in which the surfactant comprises both an alkylene polyalkylene oxide amine polymer and a polyoxyalkylene alkyl ether.

[0032] (7)

[0033] A chemical-mechanical polishing composition in any one of the compositions of (1) to (6), wherein the surfactant comprises an alkylene polyalkylene oxide amine polymer, and the alkylene polyalkylene oxide amine polymer comprises two or more repeating units containing a tertiary amine having an alkylene group and a polyalkylene oxide group bonded to an N atom.

[0034] (8)

[0035] In any one of the compositions of (1) to (7), the surfactant comprises a polyoxyalkylene alkyl ether, and the polyoxyalkylene alkyl ether has the formula (i) RO-(AO) n It is denoted as -H, where R is linear or branched C1 to C 15 A chemical-mechanical polishing composition in which A is an alkyl group, A is an alkylene group selected from the group consisting of ethylene groups, propylene groups and combinations thereof, and n represents the average number of moles added of AO, ranging from 2 to 30.

[0036] (9)

[0037] A chemical-mechanical polishing composition comprising, in any one of the compositions of (1) to (8), a water-soluble polymer comprising a polymer containing polyvinyl alcohol structural units.

[0038] (10)

[0039] A chemical-mechanical polishing composition in which the polymer containing the polyvinyl alcohol structural unit in the composition of (9) is a polyvinyl alcohol-polyalkylene oxide graft copolymer having a polyvinyl alcohol structural unit in the main chain and a polyalkylene oxide structural unit in the side chain, or a polyvinyl alcohol-polyalkylene oxide graft copolymer having a polyalkylene oxide structural unit in the main chain and a polyvinyl alcohol structural unit in the side chain.

[0040] (11)

[0041] A chemical-mechanical polishing composition in which, in any one of the compositions of (1) to (10), the abrasive is selected from the group consisting of alumina, silica, ceria, zirconia and combinations thereof.

[0042] (12)

[0043] In the composition of (1),

[0044] Silica having a primary particle size of 20 to 40 nm,

[0045] Hydroxyethylcellulose having a weight average molecular weight of 150,000 or less,

[0046] ammonia,

[0047] A surfactant comprising one or more of alkylene polyalkylene oxide amine polymers and polyoxyalkylene alkyl ethers,

[0048] A water-soluble polymer comprising a polymer containing polyvinyl alcohol structural units, and

[0049] aqueous carrier

[0050] A chemical-mechanical polishing composition comprising

[0051] (13)

[0052] A chemical-mechanical polishing composition in which the substrate is a silicon substrate in any one of the compositions of (1) to (12).

[0053] (14)

[0054] A step of contacting a substrate with a polishing pad and a chemical-mechanical polishing composition of any one of the compositions of (1) to (13),

[0055] The step of moving a polishing pad against the substrate with the chemical-mechanical polishing composition in between, and

[0056] A step of polishing the substrate by wearing away at least a portion of the substrate.

[0057] A chemical-mechanical polishing method of a substrate comprising

[0058] (15)

[0059] A chemical-mechanical polishing method of a substrate comprising, in the method of (14), a step of diluting the chemical-mechanical polishing composition and then filtering it with a filter having a pore diameter of 5 μm or less before the contacting step. Effects of the invention

[0060] According to the present invention, a chemical mechanical polishing composition comprising an abrasive, a basic component, and an aqueous carrier is provided, wherein an HEC having a low weight-average molecular weight, more specifically an HEC having a weight-average molecular weight of 200,000 or less, is used in combination with a surfactant (e.g., a nonionic surfactant), thereby providing a chemical mechanical polishing composition containing an HEC that exhibits improved POU filter filtration properties after dilution. Furthermore, according to the present invention, by performing chemical mechanical polishing using such a chemical mechanical polishing composition, the surface quality of the substrate (surface defects, nano-polishing defects) can be improved compared to when a conventional polishing composition is used. Brief explanation of the drawing

[0061] Figure 1 is a graph showing the amount of filtration according to the filtration time of the polishing composition used in the example. Figure 2 is a graph showing the amount of filtration according to the filtration time of the polishing composition used in the example. Figure 3 is a graph showing the amount of filtration according to the filtration time of the polishing composition used in the example. Specific details for implementing the invention

[0062] Chemical-Mechanical Polishing Composition

[0063] The chemical mechanical polishing composition of the present invention is for polishing a substrate, and

[0064] Abrasive,

[0065] Hydroxyethyl cellulose having a weight average molecular weight of 200,000 or less,

[0066] Basic components,

[0067] Surfactants, and

[0068] aqueous carrier

[0069] Includes

[0070] In chemical-mechanical polishing compositions for polishing substrates such as silicon wafers, cellulose derivatives commonly used as water-soluble polymers are highly useful for improving the wettability of the substrate surface to be polished. This improvement in wettability occurs because the cellulose derivatives can maintain the hydrophilicity of the substrate surface. Increased wettability between the CMP slurry and the substrate surface allows for proper interaction between the slurry and the substrate, enabling proper and uniform polishing, which in turn allows for the achievement of high surface quality (surface defects, nano-polishing defects). Furthermore, among cellulose derivatives, hydroxyethyl cellulose (HEC) is highly practical as it exhibits not only appropriate dispersibility and high solubility in water-soluble solvents but also excellent compatibility with surfactants (e.g., nonionic surfactants). Therefore, the use of HEC is highly desirable in CMP slurries used for substrate CMP, particularly for the CMP finishing polishing of silicon wafers. HEC is a type of cellulose derivative, and since naturally derived cellulose is used as a raw material, water-insoluble substances derived from cellulose may be present, and abrasives such as silica, which form aggregates on water-insoluble substances, may be adsorbed. Since HEC itself exhibits high adsorption capacity for abrasives, it has the characteristic of causing abrasive aggregation. When polishing is performed with a CMP slurry containing such aggregates, defects on the surface to be polished may increase, or nano-sized polishing scratches (nano-polishing defects) may occur, which can adversely affect the surface quality of the substrate.

[0071] To remove aggregates and impurities present in the polishing composition, filtration by a filter may be performed immediately before chemical-mechanical polishing by a CMP device. For example, a filter may be installed between the slurry supply unit and the location where the CMP device is used. Filter filtration near such usage location is called POU filter filtration, and it is an effective process for improving the surface quality of substrates such as silicon wafers; the smaller the pore diameter of the filter, the smaller aggregates can be removed by filtration, thereby further improving the surface quality of the substrate. Additionally, the polishing composition used for chemical-mechanical polishing may be diluted from its state at the time of purchase or storage according to the polishing conditions desired by the user and the specifications required by the substrate. Therefore, to ensure that filtration of the polishing composition is performed efficiently using a filter with a smaller pore diameter, it is important to suppress filter clogging to improve POU filter filtration even in the diluted slurry. Conventionally, various developments have been made to improve the filtration of the polishing composition (i.e., the filtration of the polishing composition before dilution). However, as mentioned above, the polishing composition may be diluted immediately before use for CMP. In particular, when a polishing composition containing HEC, an abrasive, and a basic component (e.g., ammonia), which is useful for CMP of silicon wafers, is diluted, the mixing ratio of the composition changes, and it is known that the polishing composition containing HEC has lower filterability after dilution compared to a polishing composition not containing HEC, as HEC is adsorbed onto an abrasive such as silica to form aggregates or forms water-insoluble substances derived from cellulose.Therefore, it is desirable to develop a chemical-mechanical polishing composition that exhibits improved POU filter filtration after dilution, and in particular, it is desirable to have high POU filter filtration that enables filtration using a filter with a small pore diameter of a chemical-mechanical polishing composition containing abrasives such as silica and basic components such as ammonia in addition to HEC, which have excellent wettability but can have an adverse effect on filtration.

[0072] Accordingly, the inventors conducted various investigations on each component of the abrasive composition to obtain an abrasive composition having high POU filter filtration properties after dilution, comprising HEC, an abrasive, and a basic component. As a result, they discovered that by using HEC having a low weight-average molecular weight—more specifically, 200,000 or less, preferably 150,000 or less—in combination with a surfactant, the abrasive composition exhibits high filter filtration properties not only before dilution but also, for example, when diluted by about 20 times. More specifically, it was discovered that by using HEC with a low molecular weight, the molecular size of the HEC itself becomes smaller, and the abrasive to which the HEC is attached and the HEC itself can easily pass through the filter. It has been discovered that by adding a surfactant to improve the dispersion stability of the polishing composition, the abrasive and HEC can be properly dispersed and easily pass through a filter. These effects of the present invention are well manifested regardless of the size of the abrasive (particularly the primary particle size), but are also adequately manifested even when used in combination with an abrasive having an average primary particle size of 20 to 40 nm, which can be preferably used in the finishing CMP polishing step of a silicon substrate. Therefore, the chemical-mechanical polishing composition according to the present invention is highly practical, particularly in the finishing polishing step of a silicon substrate. Naturally, it should be noted that the chemical-mechanical polishing composition according to the present invention can be used in other polishing steps and / or polishing of other substrates.

[0073] [Abrasive]

[0074] The abrasive of the present invention may be any suitable abrasive known to those skilled in the art of chemical-mechanical polishing of semiconductor substrates, such as silicon wafers. The abrasive may be selected from the group consisting of, for example, alumina (e.g., α-alumina, γ-alumina, δ-alumina, and fumed alumina) and silica (e.g., colloidal silica, precipitated silica, and fumed silica). It may be, but is not limited to, ceria, titania, zirconia, germania, magnesia, co-forming products thereof, and any combination thereof. The abrasive is preferably selected from the group consisting of alumina, silica, ceria, zirconia, and combinations thereof, more preferably silica, particularly colloidal silica, or ceria, and most preferably colloidal silica.

[0075] In the present invention, the abrasive may have any suitable particle size. Although not particularly limited, the abrasive may have, for example, an average primary particle size of 5 nm or more, 10 nm or more, 15 nm or more, or 20 nm or more. To obtain improved POU filter filtration performance by sufficiently suppressing aggregation of the abrasive while securing a polishing speed, the abrasive preferably has an average primary particle size of 15 nm or more, more preferably 20 nm or more. The abrasive may have an average primary particle size of 200 nm or less, 150 nm or less, 100 nm or less, 80 nm or less, 60 nm or less, 50 nm or less, or 40 nm or less. To obtain further improved POU filter filtration performance and reduce surface defects, the abrasive preferably has an average primary particle size of 50 nm or less, more preferably 40 nm or less. Accordingly, the abrasive may have an average primary particle size in the range of, for example, 5 to 200 nm, 10 to 200 nm, 20 to 200 nm, 5 to 100 nm, 10 to 100 nm, 20 to 100 nm, 5 to 50 nm, 10 to 50 nm, 20 to 50 nm, 5 to 40 nm, 10 to 40 nm, or 20 to 40 nm, and in order to further improve POU filter filtration performance, the abrasive has an average primary particle size in the range of 20 to 40 nm. Accordingly, the most preferred abrasive in the present invention is silica (e.g., colloidal silica) having an average primary particle size of 20 to 40 nm.

[0076] In addition, in terms of increasing the polishing speed and improving the surface quality of the substrate to be polished, the abrasive preferably has an average secondary particle size in the range of 0.02 to 3 μm, more preferably 0.02 to 1.0 μm, and most preferably 0.02 to 0.2 μm. The average primary particle size of the abrasive can be determined by performing image analysis on images taken with a scanning electron microscope (SEM) or a transmission electron microscope (TEM). In addition, the average secondary particle size can be measured as the volume-averaged particle size using the laser light scattering method.

[0077] The abrasive may be present in the chemical-mechanical polishing composition in an amount of 0.01 mass% or more, 0.02 mass% or more, 0.05 mass% or more, or 0.1 mass% or more, and 20 mass% or less, 15 mass% or less, 12 mass% or less, or 10 mass% or less, based on the mass of the aqueous carrier and all components dissolved or suspended therein. The abrasive is preferably present in the chemical-mechanical polishing composition in an amount ranging from 0.01 to 20 mass%, more preferably from 0.05 to 15 mass%, and most preferably from 0.1 to 10 mass%. The chemical-mechanical polishing composition in a concentrated state (before dilution) may contain, for example, 1 to 15 mass%, preferably 1 to 10 mass% of abrasive. In addition, the diluted chemical-mechanical polishing composition (when used for polishing) may contain, for example, 0.01 to 3 mass%, preferably 0.01 to 1 mass% of abrasive material.

[0078] [Hydroxyethyl cellulose (HEC)]

[0079] In the chemical-mechanical polishing composition according to the present invention, hydroxyethyl cellulose (HEC) is an essential component. HEC can primarily function as a wetting agent. Such a wetting agent is effective in maintaining the hydrophilicity of a substrate surface, such as a silicon wafer. In the present invention, it is important to set the weight-average molecular weight (Mw) of HEC low to obtain improved POU filter filtration properties. Specifically, the HEC in the present invention has an Mw of 200,000 or less, preferably 150,000 or less, and more preferably 120,000 or less. By using HEC with a low Mw in combination with the surfactant described below, a chemical-mechanical polishing composition exhibiting improved POU filter filtration properties after dilution of the polishing composition can be provided. If the molecular weight of HEC increases (e.g., Mw: 250,000), particularly during filtration after the polishing composition is diluted, the filter becomes clogged, the polishing composition is not sufficiently filtered, and the POU filter filtration properties are reduced. In such cases, the yield of the slurry usable for CMP is significantly reduced, which may impair practicality. Additionally, the filter must be cleaned or replaced after each use, and the slurry cannot be supplied periodically or continuously, which is undesirable for use.

[0080] HEC may be present in the chemical-mechanical polishing composition in an amount of, for example, 0.001 mass% or more, 0.002 mass% or more, 0.005 mass% or more, or 0.01 mass% or more, and 2.0 mass% or less, 1.5 mass% or less, 1.2 mass% or less, or 1.0 mass% or less, based on the mass of the aqueous carrier and all components dissolved or suspended therein. HEC may be present in the chemical-mechanical polishing composition in an amount of preferably 0.001 to 2.0 mass%, more preferably 0.005 to 1.5 mass%, and most preferably 0.01 to 1.0 mass%.

[0081] [Basic component]

[0082] The basic component of the present invention can chemically act on the surface of a semiconductor substrate, such as a silicon wafer, and assist in mechanical polishing together with an abrasive. The basic component is not particularly limited, but may be a compound selected from the group consisting of, for example, ammonia, potassium hydroxide, sodium hydroxide, ammonium carbonate, potassium carbonate, sodium carbonate, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, monoethanolamine, N-(β-aminoethyl)ethanolamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, piperazine anhydrous, piperazine hexahydrate, 1-(2-aminoethyl)piperazine, N-methylpiperazine, and any combination thereof. The basic component is preferably selected from the group consisting of ammonia, potassium hydroxide, sodium hydroxide, ammonium carbonate, potassium carbonate, and sodium carbonate. The basic component is more preferably ammonia, potassium hydroxide, or sodium hydroxide, and most preferably ammonia.

[0083] The basic component may be present in the chemical-mechanical polishing composition in an amount of, for example, 0.001 mass% or more, 0.002 mass% or more, 0.005 mass% or more, 0.01 mass% or more, 0.1 mass% or more, and 5.0 mass% or less, 3.0 mass% or less, 1.5 mass% or less, 1.2 mass% or less, or 1.0 mass% or less, based on the mass of the aqueous carrier and all components dissolved or suspended therein. The basic component is preferably present in the chemical-mechanical polishing composition in an amount ranging from 0.001 to 5.0 mass%, more preferably from 0.005 to 1.5 mass%, and most preferably from 0.01 to 1.0 mass%.

[0084] [Surfactant]

[0085] The surfactant of the present invention is an essential component of the chemical-mechanical polishing composition according to the present invention, but the type of surfactant may be any suitable surfactant known to those skilled in the art of chemical-mechanical polishing of semiconductor substrates such as silicon wafers. By using a combination of the surfactant and the HEC having a low weight-average molecular weight as described above, the POU filter filtration of the polishing composition after dilution can be improved. Conversely, if a surfactant is not used, the dispersibility of the polishing composition is insufficient, and even if HEC with a low weight-average molecular weight is used, the POU filter filtration of the polishing composition after dilution may become insufficient. Although not particularly limited, the surfactant may typically be an anionic surfactant or a nonionic surfactant, and preferably a nonionic surfactant. Using a nonionic surfactant as the surfactant is desirable not only for facilitating pH adjustment of the HEC but also for improving compatibility with the HEC. Excellent surface quality (e.g., haze) can be achieved by polishing a substrate, such as a silicon wafer, using a chemical-mechanical polishing composition containing a surfactant.

[0086] Examples of nonionic surfactants are not particularly limited, but include polyoxyalkylene alkyl ethers (e.g., polyoxyethylene isopropyl ether, polyoxyethylene isobutyl ether, polyoxyethylene tertiary-butyl ether, polyoxyethylene tertiary-butyl ether, polyoxyethylene isopentyl ether, polyoxyethylene isohexyl ether, polyoxyethylene heptyl ether, polyoxyethylene isoheptyl ether, polyoxyethylene isooctyl ether, polyoxyethylene isononyl ether, polyoxyethylene isodecyl ether, polyoxyethylene oxypropylene 2-propyl heptyl ether, polyoxyethylene undecyl ether, polyoxyethylene isoundecyl ether, polyoxyethylene lauryl ether, polyoxyethylene isolauryl ether, polyoxyethylene tridecyl ether, polyoxyethylene isotridecyl ether, polyoxyethylene tetradecyl ether, polyoxyethylene Isotetradecyl ether, polyoxyethylene pentadecyl ether, polyoxyethylene isopentadecyl ether, polyoxypropylene methyl ether, polyoxypropylene ethyl ether, polyoxypropylene butyl ether, and polyoxypropylene-2-ethylhexyl ether); polyoxyalkylene phenyl ethers (e.g., polyoxyethylene phenyl ether, polyoxyethylene styrene phenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, and polyoxyethylene dodecylphenyl ether); alkylene polyalkylene oxide amine polymers; polyoxyalkylene alkylamines (e.g., polyoxyethylene behenylamine, polyoxyethylene stearylamine, polyoxyethylene oleylamine, polyoxyethylene cetylamine, and polyoxyethylene laurylamine); Polyoxyalkylene alkyl amides (e.g., polyoxyethylene laurylamide, polyoxyethylene stearylamide, and polyoxyethylene oleylamide); copolymers containing ethylene oxide units (EO) and propylene oxide units (PO);Polyether polyols (e.g., polyethylene glycol, polypropylene glycol, polytetramethylene glycol, alternating copolymers of EO and PO, block copolymers of EO and PO, and random copolymers of EO and PO); polyoxyalkylene fatty acid esters (e.g., polyoxyethylene monostearate esters, polyoxyethylene distearate esters, polyoxyethylene monooleic acid esters, polyoxyethylene dioleic acid esters, and polyoxyethylene monolauric acid esters); polyethylene glycol fatty acid esters (e.g., polyethylene glycol monostearate and polyethylene glycol monooleate); glycerin fatty acid esters (e.g., lecithin, polymer emulsifiers, and oil-based glycerin monostearate); polyglycerin fatty acid esters (e.g., polyglyceryl monooleate, polyglyceryl pentaoleate, and polyglyceryl decaoleate); Polyoxyethylene glycerin fatty acid esters (e.g., polyoxyethylene glycerin monostearate); sorbitan fatty acid esters (e.g., sorbitan monolaurate, sorbitan monooleate, and sorbitan trioleate); polyoxyethylene sorbitan fatty acid esters (e.g., polyoxyethylene sorbitan monostearate and polyoxyethylene sorbitan trioleate); polyoxyethylene sorbitol fatty acid esters (e.g., polyoxyethylene sorbitol monolaurate and polyoxyethylene sorbitol tetraoleate); and polyoxyethylene castor oil / hardened castor oil (e.g., polyoxyethylene castor oil and polyoxyethylene hardened castor oil). These surfactants may be used alone or in combination of two or more.

[0087] The amount of surfactant is determined by the type of surfactant, but the surfactant is present in the chemical-mechanical composition in amounts of, for example, 0.01 ppm or more, 0.05 ppm or more, 0.1 ppm or more, 0.5 ppm or more, 1 ppm or more, 2 ppm or more, 5 ppm or more, or 10 ppm or more, and 5000 ppm or less, 3000 ppm or less, 1000 ppm or less, 500 ppm, 300 ppm or less, 1000 ppm or less, 100 ppm or less, based on the mass of the aqueous carrier and all components dissolved or suspended therein. The surfactant may be present in the chemical-mechanical polishing composition in an amount preferably of 0.1 to 5000 ppm (0.00001 to 0.5 mass%), more preferably 1 to 1000 ppm (0.0001 to 0.1 mass%), and most preferably 5 to 1000 ppm (0.0005 to 0.1 mass%).

[0088] In order to achieve further improved POU filter filtration and further improve surface quality, particularly haze reduction, the surfactant of the present invention preferably comprises one or more of alkylene polyalkylene oxide amine polymers and polyoxyalkylene alkyl ethers. More preferably, the surfactant of the present invention may comprise both alkylene polyalkylene oxide amine polymers and polyoxyalkylene alkyl ethers. Such a surfactant is a surfactant that is highly effective in reducing haze on a substrate.

[0089] (Alkylene polyalkylene oxide amine polymer)

[0090] The chemical-mechanical polishing composition of the present invention preferably comprises an alkylene polyalkylene oxide amine polymer as a surfactant to achieve further improved POU filter filtration and / or excellent haze characteristics. Furthermore, when the chemical-mechanical polishing composition of the present invention contains an alkylene polyalkylene oxide amine polymer, it is more preferable that the alkylene polyalkylene oxide amine polymer has two or more repeating structural units containing a tertiary amine having an alkylene group and a polyalkylene oxide group bonded to an N atom. As described above, by using an alkylene polyalkylene oxide amine polymer in the chemical-mechanical polishing composition according to the present invention, a greater haze reduction effect can be achieved while obtaining further improved POU filter filtration. Of course, when an alkylene polyalkylene oxide amine polymer is used in the chemical-mechanical polishing composition, it may be used in combination with other surfactants.

[0091] Alkylene oxide amine polymers are not particularly limited and are represented, for example, by the following chemical formula:

[0092] [Chemical Formula 1]

[0093]

[0094] In the above equation, R1 is linear or branched C1 to C 10 An alkylene group, preferably a linear or branched C1 to C4 alkylene group, and more preferably an ethylene group; R2 is an alkylene group selected from the group consisting of an ethylene group, a propylene group, a butylene group, and combinations thereof; x is an integer from 2 to 1000, preferably from 2 to 20; and y is an integer from 2 to 10000, preferably from 2 to 500. R2 is preferably selected from an ethylene group and / or a propylene group. When R2 includes both an ethylene group and a propylene group, it is preferable that the ethylene group and the propylene group be present in a molar ratio of 80:20 to 90:10.

[0095] The aforementioned alkylene polyalkylene oxide amine polymer preferably has a solubility parameter (SP) of 9 to 10. In the present invention, the solubility parameter (SP) is calculated using the Fedors method described in the literature [Ueda et al., Research on Paints, No. 152, October 2010, pp. 41-46].

[0096] The alkylene polyalkylene oxide amine polymer may have an average molecular weight of, for example, 5,000 to 100,000 or 10,000 to 80,000. If the average molecular weight is less than 5,000, there is a concern that sufficient haze improvement may not be achieved. Conversely, if the average molecular weight exceeds 100,000, the dependence on the additive for the effect of the alkylene polyalkylene oxide amine polymer, for example, the haze improvement effect, becomes too large and undesirable.

[0097] The alkylene polyalkylene oxide amine polymer may be included in the chemical-mechanical polishing composition in amounts, for example, at least 1 ppm, at least 2 ppm, at least 5 ppm, or at least 10 ppm, and at least 5000 ppm, at least 3000 ppm, at least 1000 ppm, or at least 500 ppm, based on the mass of the aqueous carrier and all components dissolved or suspended therein. The alkylene polyalkylene oxide amine polymer is preferably present in the chemical-mechanical polishing composition in an amount ranging from 1 to 5000 ppm (0.0001 to 0.5 mass%), more preferably from 2 to 1000 ppm (0.002 to 0.1 mass%), and most preferably from 5 to 1000 ppm (0.005 to 0.1 mass%).

[0098] Alkylene polyalkylene oxide amine polymers can be produced by any method known to those skilled in the art. For example, alkylene polyalkylene oxide amine polymers can be produced by the addition polymerization of alkylene oxides to the active hydrogen of a polyamine compound having two or more primary amino groups and / or secondary amino groups and containing 4 to 100 N atoms within the molecule. More specifically, the polyamine compound can be produced by the addition polymerization of alkylene oxides (graft polymerization) at 100 to 180°C and 1 to 10 atm in the presence of an alkali catalyst. The mode of addition polymerization of alkylene oxides to the polyamine compound is not particularly limited, and when two or more alkylene oxides are added, it may be a block type or a random type.

[0099] Examples of polyamine compounds providing a main chain structure include polyethylene polyamines such as triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, and hexaethyleneheptamine, and polyalkyleneimines such as polyethyleneimine obtained by polymerization of ethyleneimine. These compounds may be used alone, or a combination of two or more may be used to form a polyamine main chain structure. Examples of alkylene oxides added to the main chain structure include ethylene oxide, propylene oxide, and butylene oxide. These alkylene oxides may be used alone or in combination of two or more.

[0100] (Polyoxyalkylene alkyl ether)

[0101] The chemical mechanical polishing composition of the present invention preferably contains a polyoxyalkylene alkyl ether as a surfactant to obtain further improved POU filter filtration and / or excellent haze characteristics. Polyoxyalkylene alkyl ethers may be included as an alternative to the aforementioned alkylene polyalkylene oxide amine polymers, or both may be included; however, from the perspective of improving POU filter filtration and / or haze characteristics, it is most preferable to include both. Of course, when polyoxyalkylene alkyl ethers are used in the chemical mechanical polishing composition, they may be used in combination with other surfactants. Furthermore, when the chemical mechanical polishing composition of the present invention contains polyoxyalkylene alkyl ethers, the polyoxyalkylene alkyl ethers may include polyoxyalkylene alkyl ethers represented by the formula (i)RO-(AO)nH, where R is a linear or branched C1 to C 15 A is an alkyl group, A is an alkylene group selected from the group consisting of ethylene groups, propylene groups, and combinations thereof, and n represents the average number of moles added to AO, ranging from 2 to 30. By including such polyoxyalkylene alkyl ethers as additive components, not only can the filtration performance of the POU filter be improved, but substrate surface haze can also be reduced compared to cases where polyoxyalkylene alkyl ethers are not included, and furthermore, a decrease in the wettability of the substrate surface resulting from the accumulation of additive components such as polyoxyalkylene alkyl ethers on the polishing pad can be substantially or completely prevented. Therefore, when a chemical-mechanical polishing composition containing polyoxyalkylene alkyl ethers is used, the occurrence of surface defects due to a decrease in the wettability of the substrate surface can be reliably prevented, thereby improving the lifespan of the polishing pad.

[0102] Even when the number of carbon atoms in the R group of formula (i) is 16 or more, the haze on the substrate surface can be reduced in relation to certain polyoxyalkylene alkyl ethers. However, when the number of carbon atoms in the R group of formula (i) is 16 or more, such polyoxyalkylene alkyl ethers, for example, polyoxyethylene cetyl ether or polyoxyethylene stearyl ether, easily accumulate on the polishing pad, and in some cases, the polyoxyalkylene alkyl ethers cannot be completely removed by pad conditioning performed before each polishing process. Therefore, there is a risk that polyoxyalkylene alkyl ethers will gradually accumulate on the polishing pad during repeated substrate polishing. The accumulated polyoxyalkylene alkyl ethers reduce the wettability of the substrate surface and, by themselves, can cause defects on the substrate surface during polishing. Furthermore, if the wettability of the substrate surface is reduced, polishing debris and other foreign substances are more likely to adhere to the substrate, and as a result, may cause defects on the substrate surface.

[0103] Accordingly, in the present invention, R of chemical formula (i) is linear or branched C1 to C 15 It may be an alkyl group, and to reduce substrate surface haze and more reliably prevent the reduction in substrate surface wettability due to the accumulation of polyoxyalkylene alkyl ethers on the polishing pad, R is preferably a linear or branched C1 to C 13 It is an alkyl group. In addition, in another preferred embodiment of the present invention, R is a branched C 11 to C 15 Alkyl group, branched C 12 to C 14 Alkyl groups, or branched C 13 It may be an alkyl group (e.g., an isotridecyl group).

[0104] A of chemical formula (i) may be either an ethylene group or a propylene group, or any combination of one or more ethylene groups and one or more propylene groups. In a particular preferred embodiment of the present invention, A is an ethylene group or a combination of an ethylene group and a propylene group.

[0105] In chemical formula (i), n represents the average number of moles of added AO and can be appropriately determined, for example, within the range of 2 to 30. From the perspective of preventing a decrease in the wettability of the substrate surface due to the accumulation of polyoxyalkylene alkyl ethers on the polishing pad, a larger value of n is preferred and can be, for example, 5 or more, 6 or more, 8 or more, 10 or more, 11 or more, or 12 or more. Additionally, n can be 28 or less, for example, 25 or less, or 23 or less. Furthermore, in the present invention, “average number of moles of added AO” also refers to the average value of the number of moles of oxyalkylene units contained in 1 mole of polyoxyalkylene alkyl ether.

[0106] Specific examples of the above polyoxyalkylene alkyl ethers are not particularly limited, but include polyoxyethylene isopropyl ether, polyoxyethylene isobutyl ether, polyoxyethylene tertiary-butyl ether, polyoxyethylene isopentyl ether, polyoxyethylene isohexyl ether, polyoxyethylene heptyl ether, polyoxyethylene isoheptyl ether, polyoxyethylene isooctyl ether, polyoxyethylene isononyl ether, polyoxyethylene isodecyl ether, polyoxyethylene oxypropylene 2-propyl heptyl ether, polyoxyethylene undecyl ether, polyoxyethylene isoundecyl ether, polyoxyethylene lauryl ether, polyoxyethylene isolauryl ether, polyoxyethylene tridecyl ether, polyoxyethylene isotridecyl ether, polyoxyethylene tetradecyl ether, and polyoxyethylene isotetradecyl ether. It includes ethers, polyoxyethylene pentadecyl ethers, and polyoxyethylene isopentadecyl ethers.

[0107] The above polyoxyalkylene alkyl ether preferably comprises one or more of polyoxyethylene isodecyl ether, polyoxyethylene oxypropylene 2-propyl heptyl ether, polyoxyethylene lauryl ether, and polyoxyethylene isotridecyl ether, and most preferably polyoxyethylene oxypropylene 2-propyl heptyl ether and polyoxyethylene isotridecyl ether. These polyoxyalkylene alkyl ethers can be synthesized by any method known to those skilled in the art or are commercially available.

[0108] In the present invention, the HLB value of a polyoxyalkylene alkyl ether is calculated according to the Griffin method, and more specifically, by the following formula:

[0109] HLB value = 20 x (Sum of formula weights of hydrophilic components) / (Molecular weight).

[0110] The hydrophilic component of the polyoxyalkylene alkyl ether is polyoxyalkylene, i.e., (AO) of formula (i) n Since this corresponds to a portion, it is evident that the HLB value depends on the number of carbon atoms in the R group and the average moles of added oxyalkylene (AO). However, regarding the effects of the present invention, particularly the improvement of substrate surface wettability, since the number of carbon atoms in the R group of formula (i) is the dominant parameter, the substrate surface wettability is not significantly affected by the HLB value. Therefore, the polyoxyalkylene alkyl ether of the present invention can have any suitable HLB value. Generally, the HLB value can be appropriately determined within the range of 12 to 18.

[0111] In the present invention, the polyoxyalkylene alkyl ether may have any suitable molecular weight. Although not particularly limited, the polyoxyalkylene alkyl ether may have an average molecular weight of about 100 to about 2,000.

[0112] Polyoxyalkylene alkyl ethers may be present in the chemical-mechanical polishing composition in amounts of, for example, 0.01 ppm or more, 0.02 ppm or more, 0.05 ppm or more, or 0.1 ppm or more, and 5000 ppm or less, 3000 ppm or less, 1000 ppm or less, or 500 ppm or less, based on the mass of the aqueous carrier and all components dissolved or suspended therein. Polyoxyalkylene alkyl ethers are preferably present in the chemical-mechanical polishing composition in an amount ranging from 0.1 to 5000 ppm (0.00001 to 0.5 mass%), more preferably from 0.1 to 1000 ppm (0.00001 to 0.1 mass%), and most preferably from 0.1 to 500 ppm (0.00001 to 0.05 mass%).

[0113] [Aqueous carrier]

[0114] An aqueous carrier is used to facilitate the application of all components dissolved or suspended in the aqueous carrier to a suitable substrate surface to be polished. The aqueous carrier may typically consist only of water, may include water and a water-soluble solvent, or may be an emulsion. It is preferable to use an alcohol, for example, methanol or ethanol, as the water-soluble solvent. The aqueous carrier is preferably water, and more preferably deionized water.

[0115] The chemical-mechanical polishing composition of the present invention may have any suitable pH, and a specific pH may be appropriately determined considering the polishing speed, etc. For example, the chemical-mechanical polishing composition may have a pH of 7 to 12, preferably 8 to 12, and more preferably 8.5 to 12. The pH value may be adjusted by adding a pH adjuster as needed. The pH adjuster may be any alkaline substance and may be the same as or different from the basic component. The pH adjuster is preferably selected from the group consisting of ammonia, potassium hydroxide, sodium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonium bicarbonate, ammonium carbonate, potassium bicarbonate, potassium carbonate, sodium bicarbonate, and sodium carbonate. The pH adjuster is more preferably ammonia, potassium hydroxide, sodium hydroxide, tetramethylammonium hydroxide, or tetraethylammonium hydroxide, and most preferably potassium hydroxide.

[0116] [Water-soluble polymer]

[0117] The chemical-mechanical polishing composition of the present invention may optionally further include a water-soluble polymer in addition to HEC. Although not particularly limited, the water-soluble polymer may be one or more selected from the group consisting of polyvinylpyrrolidone (PVP), polyvinylacetamide, cellulose derivatives (excluding HEC), and polymers containing polyvinyl alcohol structural units, and preferably includes a polymer containing polyvinyl alcohol structural units.

[0118] The amount of water-soluble polymer (excluding HEC) is determined by the type of water-soluble polymer used, but the water-soluble polymer may be present in the chemical-mechanical polishing composition in an amount of, for example, 0.1 ppm or more, 1 ppm or more, 2 ppm or more, 5 ppm or more, 10 ppm or more, 20 ppm or more, or 50 ppm or more, and 5000 ppm or less, 3000 ppm or less, 1000 ppm or less, or 500 ppm or less, based on the mass of the aqueous carrier and all components dissolved or suspended therein. The water-soluble polymer may be present in the chemical-mechanical polishing composition in an amount of preferably 0.1 to 5000 ppm (0.00001 to 0.5 mass%), more preferably 1 to 3000 ppm (0.0001 to 0.3 mass%), and most preferably 2 to 1000 ppm (0.0002 to 0.1 mass%).

[0119] (Cellulose derivative)

[0120] In cases where a cellulose derivative other than HEC is used as a water-soluble polymer, the cellulose derivative may be selected from methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and combinations thereof.

[0121] (Polymer containing polyvinyl alcohol structural units)

[0122] In chemical-mechanical polishing using mechanical interaction between a substrate and a polishing composition (slurry), continuous surface defects such as nano-polishing defects or PID may occur on the substrate due to abrasives contained in the slurry and / or other particles aggregated in the slurry when polishing is performed. In the present invention, to reduce continuous surface defects on the substrate such as nano-polishing defects or PID, the chemical-mechanical polishing composition may include a polymer containing polyvinyl alcohol structural units.

[0123] Polymers containing polyvinyl alcohol structural units can act as wetting agents. Therefore, in the chemical-mechanical polishing composition of the present invention, a polymer containing polyvinyl alcohol structural units in addition to HEC may be used to maintain the hydrophilicity of the substrate surface. Furthermore, in the polishing composition, it is preferable that the polymer containing polyvinyl alcohol structural units be used together with one or more of the aforementioned alkylene polyalkylene oxide amine polymers and polyoxyalkylene alkyl ethers, and it is even more preferable that it be used together with both alkylene polyalkylene oxide amine polymers and polyoxyalkylene alkyl ethers. By using the polymer together with such surfactants, the quality of the slurry is better stabilized.

[0124] A polymer containing polyvinyl alcohol structural units may be any polymer containing polyvinyl alcohol structural units. For example, a polymer containing polyvinyl alcohol structural units may be simply polyvinyl alcohol, or it may be a polymer containing polyalkylene oxides such as polyethylene glycol in addition to polyvinyl alcohol. Additionally, a polymer containing polyvinyl alcohol structural units may, for example, include polyvinyl alcohol structural units in the main chain or side chain of the polymer, and some of the polyvinyl alcohol structural units may be substituted with acyloxy groups. An example of a polymer containing polyvinyl alcohol structural units in the polymer main chain includes a polyvinyl alcohol-polyalkylene oxide graft copolymer containing polyvinyl alcohol structural units in the polymer main chain and polyalkylene oxide structural units in the side chain, wherein the polyalkylene oxide structural units may include one or more selected from the group consisting of ethylene oxide, propylene oxide, and combinations thereof. In such copolymers, polyvinyl alcohol structural units and polyalkylene oxide structural units may be present in a molar ratio of, for example, 95:5 to 60:40, or 90:10 to 70:30.

[0125] A preferred example of such a copolymer includes a polyvinyl alcohol-polyethylene oxide graft copolymer represented by the following chemical formula:

[0126] [Chemical Formula 2]

[0127]

[0128] In the above equation, R 3 is an acyloxy group represented by a hydroxyl group or R'COO- (where R' is a C1 to C8 alkyl group) (e.g., a CH3COO- group), and R 4is a hydrogen atom, or an acyl group represented by R''CO- (where R'' is a C1 to C8 alkyl group) (e.g., a CH3CO- group), a is an integer from 1 to 10,000, M1 and M2 are real numbers from 0 mol% to 100 mol%, and M1 + M2 = 100 mol%. The copolymer of the above chemical formula is R 3 The structure may have a mixture of hydroxyl groups and acyloxy groups, more specifically, a structure in which a portion of the acyloxy group is saponified into a hydroxyl group. In this case, the degree of saponification is not particularly limited and may be 70 to 100%, 80 to 100%, 90 to 100%, or 95 to 100%. The values ​​of M1 and M2 may be appropriately determined according to the ratio of the presence of polyvinyl alcohol structural units constituting the main chain and polyethylene oxide structural units constituting the side chain.

[0129] A more specific example of the polyvinyl alcohol-polyethylene oxide graft copolymer of the above chemical formula includes a polyvinyl alcohol-polyethylene oxide graft copolymer represented by the following chemical formula:

[0130] [Chemical Formula 3]

[0131]

[0132] In the above formula, a is an integer from 1 to 10,000, M1 and M2 are real numbers from 0 mol% to 100 mol%, and M1 + M2 = 100 mol%. A portion of the hydroxyl group of the polyvinyl alcohol structural unit constituting the main chain of the above formula may be substituted with an acyloxy group represented by R'COO- (where R' is a C1 to C8 alkyl group), and similarly, a portion of the terminal hydroxyl group of the polyethylene oxide structural unit constituting the side chain of the above formula may be substituted with an acyl group represented by R''CO- (where R'' is a C1 to C8 alkyl group).

[0133] Examples of polymers containing polyvinyl alcohol structural units in polymer side chains include a polyvinyl alcohol-polyalkylene oxide graft copolymer containing polyalkylene oxide structural units in a main chain and polyvinyl alcohol structural units in a side chain, wherein the polyalkylene oxide structural units may include one or more selected from the group consisting of ethylene oxide, propylene oxide, and combinations thereof. In such copolymers, the polyvinyl alcohol structural units and polyalkylene oxide structural units may be present in a molar ratio of, for example, 95:5 to 60:40 or 90:10 to 70:30.

[0134] Preferred examples of such copolymers include, for example, polyvinyl alcohol-polyethylene oxide graft copolymers represented by the following chemical formula:

[0135] [Chemical Formula 4]

[0136]

[0137] In the above equation, R 5 is a hydroxyl group or an acyloxy group represented as R'COO- (wherein R' is C1 to It is a C8 alkyl group (e.g., a CH3COO- group), and R 6 and R 7Each is independently a linear or branched C2 to C3 alkylene group, b is an integer from 2 to 10,000, N1 and N2 are real numbers from 0 mol% to 100 mol%, and N1 + N2 = 100 mol%. The copolymer of the above formula may have a structure in which R is a mixture of hydroxyl groups and acyloxy groups, more specifically, a structure in which a portion of the acyloxy group is saponified into a hydroxyl group. In this case, the degree of saponification is not particularly limited and may be 70 to 100%, 80 to 100%, 90 to 100%, or 95 to 100%. The values ​​of N1 and N2 may be appropriately determined according to the ratio of the presence of polyethylene oxide structural units constituting the main chain and polyvinyl alcohol structural units constituting the side chain.

[0138] A more specific example of the polyvinyl alcohol-polyethylene oxide graft copolymer of the above chemical formula includes a polyvinyl alcohol-polyethylene oxide graft copolymer represented by the following chemical formula:

[0139] [Chemical Formula 5]

[0140]

[0141] In the above formula, b is an integer from 2 to 10,000, N1 and N2 are real numbers from 0 mol% to 100 mol%, and N1 + N2 = 100 mol%. Some of the hydroxyl groups of the polyvinyl alcohol structural units constituting the side chains of the above formula may be substituted with acyloxy groups represented by R'COO- (where R' is a C1 to C8 alkyl group).

[0142] If the polymer containing polyvinyl alcohol structural units is polyvinyl alcohol or a mixture of polyvinyl alcohol and polyalkylene oxide, the average molecular weight of the polyvinyl alcohol and polyalkylene oxide may be, for example, 1,000 to 10,000,000. Conversely, if the polymer containing polyvinyl alcohol structural units is the aforementioned polyvinyl alcohol-polyethylene oxide graft copolymer, the polyvinyl alcohol-polyethylene oxide graft copolymer may have an average molecular weight of, for example, 5,000 to 500,000, 10,000 to 300,000, or 10,000 to 200,000.

[0143] A polymer containing polyvinyl alcohol structural units may be present in a chemical-mechanical polishing composition in an amount of, for example, 0.1 ppm or more, 1 ppm or more, 2 ppm or more, or 5 ppm or more, and 5000 ppm or less, 3000 ppm or less, 1000 ppm or less, or 500 ppm or less, based on the mass of the aqueous carrier and all components dissolved or suspended therein. The polymer containing polyvinyl alcohol structural units is preferably present in the chemical-mechanical polishing composition in an amount ranging from 0.1 to 5000 ppm (0.00001 to 0.5 mass%), more preferably from 1 to 3000 ppm (0.0001 to 0.3 mass%), and most preferably from 2 to 1000 ppm (0.0002 to 0.1 mass%).

[0144] [Other Additives]

[0145] The chemical-mechanical polishing composition according to the present invention may optionally further include other additives, e.g., polishing rate accelerators and chelating agents. Examples of polishing rate accelerators include hydroxamic acid (e.g., acetohydroxamic acid), nitrogen-containing heterocyclic compounds (e.g., triazoles such as 1,2,4-triazole), and combinations thereof. Examples of chelating agents include organic acids such as oxalic acid, citric acid, malonic acid, succinic acid, glutaric acid, adipic acid, tartaric acid, and phthalic acid; amino acids such as glycine, serine, proline, leucine, alanine, asparagine, glutamine, valine, and lysine; and polyamine composites such as ethylenediaminetetraacetic acid (EDTA), hydroxyethylethylenediaminetriacetic acid (HEDTA), nitrilotriacetic acid, iminodiaacetic acid, and diethylenetriaminepentaacetic acid (DTPA).

[0146] [Chemical-mechanical polishing method for substrates]

[0147] The chemical-mechanical polishing method of the substrate of the present invention

[0148] A step of contacting a substrate with a polishing pad and the aforementioned chemical-mechanical polishing composition,

[0149] A step of moving a polishing pad against a substrate with a chemical-mechanical polishing composition in between, and

[0150] A step of polishing the substrate by wearing away at least a portion of the substrate

[0151] Includes

[0152] The chemical-mechanical polishing method of the substrate according to the present invention is particularly suitable when used with a chemical-mechanical polishing (CMP) device. Generally, such a device comprises a platen having a speed resulting from movement, rotation, and linear or circular motion during use; a polishing pad that contacts the platen and moves together with the platen as the platen moves; and a carrier that contacts the surface of the polishing pad and moves against the surface to fix the substrate to be polished. Substrate polishing is performed by contacting the polishing pad and the chemical-mechanical polishing composition of the present invention with the substrate, and then the polishing pad moves against the substrate so that at least a portion of the substrate is worn away and the substrate is polished.

[0153] The substrate may be planarized or polished with any suitable polishing pad and chemical-mechanical polishing composition. The substrate may be a silicon substrate, as well as a polysilicon film, a SiO2 film, Alternatively, it may be a silicon substrate, sapphire substrate, SiC substrate, GaAs substrate, GaN substrate, or a substrate for forming TSVs on which a metal wiring film is formed. Examples of suitable polishing pads include woven and nonwoven polishing pads. Additionally, suitable polishing pads may include suitable polymers having various densities, hardness, thickness, compressibility, compression resistance, and compression moduli. Examples of suitable polymers include polyvinyl chloride, polyvinyl fluoride, nylon, fluorocarbon, polycarbonate, polyester, polyacrylate, polyether, polyethylene, polyamide, polyurethane, polystyrene, polypropylene, co-formed products thereof, and mixtures thereof.

[0154] In addition to the method of preparing a slurry of a chemical-mechanical polishing composition in advance and performing polishing with a polishing pad while supplying the slurry to a substrate, the method of the present invention may also be performed by supplying a diluent and a slurry stock solution to a polishing pad and preparing a polishing slurry near the polishing pad.

[0155] The present invention will be explained in more detail below by way of examples. However, the present invention is not limited by these examples in any way.

[0156] Examples

[0157] In the following examples, various chemical-mechanical polishing compositions were prepared, and the POU filter filtration performance of each composition was evaluated by performing filter filtration tests using their diluted products; for some chemical-mechanical polishing compositions, light point defects (LPD) and nano-polishing defects on the surface to be polished were also evaluated when polishing silicon wafers.

[0158] [Preparation of the polishing composition of Example 1]

[0159] The polishing composition of Example 1 was prepared by adding 5.0 mass% of colloidal silica (average primary particle diameter: about 25 nm, average secondary particle diameter: about 45 nm), 0.20 mass% of ammonia, 0.28 mass% of HEC (weight average molecular weight: 120,000), and 0.050 mass% of alkylene polyalkylene oxide amine polymer (ethylene oxide:propylene oxide = 8:2, average nitrogen number: 5, molecular weight: 46,000) to water.

[0160] [Preparation of the polishing composition of Example 2]

[0161] The polishing composition of Example 2 was prepared in the same manner as the polishing composition of Example 1, except that the alkylene polyalkylene oxide amine polymer of the polishing composition of Example 1 was changed to 0.005 mass% of polyoxyethylene isotridecyl ether (carbon chain length: 13, branched chain, ethylene oxide = 8).

[0162] [Preparation of the polishing composition of Example 3]

[0163] The polishing composition of Example 3 was prepared in the same manner as the polishing composition of Example 1, except that 0.005 mass% of polyoxyethylene isotridecyl ether (carbon chain length: 13, branched chain, ethylene oxide = 8) and 0.010 mass% of polyvinyl alcohol-polyethylene oxide graft copolymer (80:20 mol%, molecular weight: 93,600, degree of saponification: 98.5%, main chain: polyvinyl alcohol, side chain: polyethylene oxide) were added to the polishing composition of Example 1 as water-soluble polymers.

[0164] [Preparation of the polishing composition of Comparative Example 1]

[0165] The polishing composition of Comparative Example 1 was prepared by adding 5.0 mass% of colloidal silica (average primary particle diameter: about 25 nm, average secondary particle diameter: about 45 nm), 0.20 mass% of ammonia, and 0.28 mass% of HEC (weight average molecular weight: 250,000) to water.

[0166] [Preparation of the polishing composition of Comparative Example 2]

[0167] The polishing composition of Comparative Example 2 was prepared in the same manner as the polishing composition of Comparative Example 1, except that the weight average molecular weight of HEC in the polishing composition of Comparative Example 1 was changed from 250,000 to 120,000.

[0168] [Preparation of the polishing composition of Comparative Example 3]

[0169] The polishing composition of Comparative Example 3 was prepared in the same manner as the polishing composition of Comparative Example 1, except that 0.050 mass% of the alkylene polyalkylene oxide amine polymer, 0.005 mass% of the polyoxyethylene isotridecyl ether, and 0.010 mass% of the polyvinyl alcohol-polyethylene oxide graft copolymer used in Example 3 were added to the components of the polishing composition of Comparative Example 1.

[0170] The compositions of the polishing compositions of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1 below. In the table, “silica size” indicates the average primary particle size of colloidal silica, “HEC Mw” indicates the weight average molecular weight of HEC, “surfactant A” indicates an alkylene polyalkylene oxide amine polymer, and “surfactant B” indicates a polyoxyethylene isotridecyl ether.

[0171]

[0172] Next, the average primary particle size of the colloidal silica was changed to prepare the polishing compositions of Example 4 and Comparative Examples 4 to 6 and the following Example 5 and Comparative Example 7 in the same manner as the polishing compositions of Examples 1 to 3 and Comparative Examples 1 to 3.

[0173]

[0174]

[0175] [POU Filter Filtration Evaluation]

[0176] Each of the polishing compositions listed in Tables 1 to 3 above was diluted 20-fold with deionized water, and a filter filtration evaluation was performed on the polishing compositions after dilution, and the POU filter filtration performance was evaluated. “Ultipore” manufactured by Nippon Pole Co., Ltd. ®Filtration was performed using an N66” (diameter: 47 mm, rated filtration accuracy: 0.2 μm) at an evaluation temperature (20°C) and a filtration differential pressure (100 kPa (constant pressure filtration)). For each abrasive composition, filter filtration evaluation was performed under the above conditions, and the filtration amount (throughput) (g) was evaluated as a function of time (seconds) after the start of filtration. The results obtained for each abrasive composition in Tables 1 to 3 are shown in Figures 1 to 3.

[0177] Referring to Table 1 and Figure 1, it can be seen that Examples 1 to 3, which used HEC with an Mw of 200,000 or less together with a surfactant, showed an increase in filtration amount over time and improved POU filter filtration performance compared to Comparative Examples 1 to 3, which used HEC with an Mw greater than 200,000 and / or did not use a surfactant. More specifically, when comparing the filtration amount (throughput) after 600 seconds for the compositions (Example 1: 401 g, Example 2: 219 g, Example 3: 353 g, Comparative Example 1: 18 g, Comparative Example 2: 165 g, and Comparative Example 3: 20 g), it was found that Examples 1 to 3 had superior POU filter filtration performance compared to Comparative Examples 1 to 3. In particular, POU filter filtration performance was significantly improved when using an alkylene polyalkylene oxide amine polymer.

[0178] Referring to Table 2 and Fig. 2, even when the average primary particle size of the abrasive is 35 nm as in Fig. 1, Example 4, which uses an HEC having an Mw of 200,000 or less together with a surfactant, has an Mw greater than 200,000. WIt was understood that the POU filter filtration performance was improved compared to Comparative Examples 4 to 6, which used HEC having [the substance] and / or did not use a surfactant. More specifically, when comparing the filtration amount (throughput) after 600 seconds (Example 4: 479 g, Comparative Example 4: 18 g, Comparative Example 5: 276 g, and Comparative Example 6: 232 g), it was found that Example 4 had superior POU filter filtration performance compared to Comparative Examples 4 to 6.

[0179] Referring to Table 3 and Figure 3, as illustrated in Figures 1 and 2, even when the average primary particle size of the abrasive is 15 nm, it can be seen that Example 5, which uses HEC with an Mw of 200,000 or less together with a surfactant, has improved POU filter filtration performance compared to Comparative Example 7, which does not use a surfactant. More specifically, when comparing the filtration amount (throughput) after 600 seconds (Example 5: 199 g and Comparative Example 7: 40 g), it was found that Example 5 had superior POU filter filtration performance compared to Comparative Example 7.

[0180] In the polishing composition according to the present invention using HEC and a surfactant with a low weight-average molecular weight, filter clogging can be sufficiently suppressed despite the polishing composition containing HEC, and sufficient POU filter filtration performance can be achieved even when using a filter with a small pore size. Furthermore, when comparing filtration performance between silica sizes with the same component composition, it was found that filtration performance is superior as the primary particle size increases. An optimal particle size can be selected (used) according to the balance between desired filtration performance and polishing performance. For example, when the surface quality of the substrate is more important, it is preferable to use silica with a small primary particle size.

[0181] [Surface Quality Evaluation After CMP]

[0182] The polishing composition of Example 3 and the polishing composition of Comparative Example 3 were diluted 20 times with deionized water, and each polishing composition after dilution was filtered with the filter described above. Then, chemical-mechanical polishing (CMP) was performed on a silicon wafer substrate using the filtered slurry, and the surface quality (light spot defects (LPD), nano-polishing defects) of the silicon wafer after polishing was evaluated.

[0183] [Grinding work]

[0184] First, a resistivity of 0.1 to 100 Ω·cm and <100> A 12-inch p-type silicon wafer (silicon substrate) having a crystal orientation was washed with hydrofluoric acid (0.5%) at 23°C for 2 minutes to remove the natural oxide film, and then the obtained silicon wafer was chemically and mechanically polished under the following conditions using a slurry prepared by diluting the polishing composition of Example 3 and the polishing composition of Comparative Example 3 with pure water 20 times (by mass). The pH of the diluted slurry was adjusted to about 10 with potassium hydroxide.

[0185] (1) CMP device: 12-inch single-sided polisher, Okamoto Machine Works SPP800S

[0186] (2) Wafer head: Template method

[0187] (3) Polishing pad: POLYPAS 27NX-PS, Fujibo Ehime Company Limited.

[0188] (4) Plate rotation speed: 31 rpm

[0189] (5) Grinding head rotation speed: 33 rpm

[0190] (6) Grinding pressure: 2.2 psi = 152 g / cm 2 = 15 kPa

[0191] (7) Slurry feed rate: 500 mL / min (free-flow)

[0192] After polishing, the silicon wafer was batch-washed at 23°C for 20 minutes using SC-1 (ammonia solution (29 mass% aqueous solution): hydrogen peroxide (31 mass% aqueous solution): pure water = 2 : 1 : 10 (volume ratio)). Then, the silicon wafer was scrubbed at 23°C using SC-200S manufactured by Shibaura Mechatronics and SC-1 (ammonia solution (29 mass% aqueous solution): hydrogen peroxide (31 mass% aqueous solution): pure water = 1 : 4 : 20 (volume ratio)) and a PVA brush, and then rinsed with pure water.

[0193] [Defect Measurement]

[0194] In addition, the formation of LPDs (bright spot defects) in polished silicon was investigated. More specifically, for LPDs, a Surfscan SP2 manufactured by KLA Tencor was also used, and LPD values ​​in the dark field composite oblique incident channel (DCO) were utilized. Nano-polishing defects were defined as the amount of signal having a scattering intensity that is less intense than the LPD signal and locally stronger than the baseline intensity. The corresponding signals observed in the defined area were counted and evaluated.

[0195] In the polishing composition of Example 3, compared to the polishing composition of Comparative Example 3, the presence of nano-polishing defects was improved by about 8% and the presence of LPD was improved by about 2% while maintaining an equivalent polishing speed. Therefore, the chemical-mechanical polishing composition according to the present invention can not only have high POU filter filtration and high practicality but also improve the surface quality of the substrate.

Claims

Claim 1 A chemical-mechanical polishing composition for polishing a substrate comprises an abrasive having a primary particle size of 20 to 40 nm, hydroxyethyl cellulose having a weight average molecular weight of 200,000 or less, a basic component, a surfactant comprising both an alkylene polyalkylene oxide amine polymer and a polyoxyalkylene alkyl ether, and an aqueous carrier, wherein the alkylene polyalkylene oxide amine polymer contains two or more repeating units containing a tertiary amine having an alkylene group and a polyalkylene oxide group bonded to an N atom, and the polyoxyalkylene alkyl ether has the chemical formula (i) RO-(AO) n It is denoted as -H, where R is branched C 11 to C 15 A chemical-mechanical polishing composition, wherein A is an alkyl group, A is an alkylene group selected from the group consisting of ethylene groups, propylene groups, and combinations thereof, and n represents the average number of moles added of AO, ranging from 2 to 30. Claim 2 A chemical-mechanical polishing composition according to claim 1, wherein the hydroxyethyl cellulose has a weight average molecular weight of 150,000 or less. Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 delete Claim 9 A chemical-mechanical polishing composition according to claim 1, further comprising a water-soluble polymer comprising a polymer containing polyvinyl alcohol structural units. Claim 10 A chemical-mechanical polishing composition according to claim 9, wherein the polymer containing the polyvinyl alcohol structural unit is a polyvinyl alcohol-polyalkylene oxide graft copolymer having a polyvinyl alcohol structural unit in the main chain and a polyalkylene oxide structural unit in the side chain, or a polyvinyl alcohol-polyalkylene oxide graft copolymer having a polyalkylene oxide structural unit in the main chain and a polyvinyl alcohol structural unit in the side chain. Claim 11 A chemical-mechanical polishing composition according to claim 1, wherein the abrasive is selected from the group consisting of alumina, silica, ceria, zirconia, and combinations thereof. Claim 12 In claim 1, the invention comprises silica having a primary particle size of 20 to 40 nm, hydroxyethyl cellulose having a weight average molecular weight of 150,000 or less, ammonia, a surfactant comprising both an alkylene polyalkylene oxide amine polymer and a polyoxyalkylene alkyl ether, a water-soluble polymer comprising a polymer containing a polyvinyl alcohol structural unit, and an aqueous carrier, wherein the alkylene polyalkylene oxide amine polymer comprises two or more repeating units containing a tertiary amine having an alkylene group bonded to an N atom and a polyalkylene oxide group, and the polyoxyalkylene alkyl ether has the chemical formula (i) RO-(AO) n It is denoted as -H, where R is branched C 11 to C 15 A chemical-mechanical polishing composition, wherein A is an alkyl group, A is an alkylene group selected from the group consisting of ethylene groups, propylene groups, and combinations thereof, and n represents the average number of moles added of AO, ranging from 2 to 30. Claim 13 A chemical-mechanical polishing composition according to claim 1, wherein the substrate is a silicon substrate. Claim 14 A method for chemically mechanical polishing of a substrate, comprising the steps of: contacting a substrate with a polishing pad and a chemically mechanical polishing composition of any one of claims 1, 2 and 9 to 13; moving the polishing pad with respect to the substrate with the chemically mechanical polishing composition in between; and polishing the substrate by abrading at least a portion of the substrate. Claim 15 A method for chemically mechanical polishing of a substrate according to claim 14, wherein, prior to the contacting step, the method comprises the step of diluting the chemically mechanical polishing composition and then filtering it through a filter having a pore diameter of 5 μm or less.

Citation Information

Patent Citations

  • Polishing composition

    JP2019127585A

  • Polishing composition and polishing method

    KR101374039B1

  • Polishing composition, polishing method using same, and substrate production method

    KR1020140012070A

  • Slurry composition and method for polishing substrate

    KR1020160135752A

  • Polishing composition

    KR1020180070586A